The Amplatzer duct occluder II additional sizes device for transcatheter PDA closure: Initial experience. Issue 7 (4th March 2014) - Bruckheimer, Elchanan; Godfrey, Max; Dagan, Tamir; Levinzon, Michael; Amir, Gabriel; Birk, Einat
<x xml:space="preserve">Abstract</x> Objectives To present our initial experience with the Amplatzer Duct Occluder II Additional Sizes (ADOIIAS) device. Background The ADOIIAS is a modified PDA closure device of various lengths and widths with small disks to avoid flow disturbance in the pulmonary arteries and descending aorta. Methods Patient population: All patients who underwent attempted closure with an ADOIIAS device at our institution Catheterization Following aortography the PDA was closed using a 4–5Fr delivery system from the pulmonary or aortic side with an ADOIIAS. Aortography to confirm position and leak was performed before and after device release. Echocardiography was performed before discharge the following day. Results Between June 2011 and December 2012, 60 patients [33 female], median age 3.3 yrs [0.6–15.8 years], and weight 14.5 kg [4–79] underwent attempted PDA closure with an ADOIIAS device. 56/60 [93.3%] ADOIIAS devices were successfully deployed [52 aortic side]. In 55/56 [98.2%], the PDA was closed on follow up echocardiogram usually on the next day. In one case, there was a small residual PDA of no hemodynamic significance on follow up. In four cases, the ADOIIAS was unstable, including one device embolization which was retrieved with no sequelae, and the PDA was closed in all cases with an alternative device in the same procedure. The mean ratio of ADOIIAS height:PDA pulmonary diameter was 2.4 ± 0.5:1. Conclusions We report a large single‐center experience with the new ADOIIAS device which proved to be versatile, safe, effective, and easy to use in the appropriate ductal anatomy. © 2014 Wiley Periodicals, Inc.